A lower duodenal immune response is associated with an increase of insulin resistance in patients with morbid obesity - Ho-Plagaro, Ailec; Santiago-Fernandez, Concepción; García-Serrano, Sara; Rodriguez, Cristina; Garrido-Sanchez, Lourdes; Escamilla, Alejandro; Gonzalo, Montserrat; Montiel-Casado, Custodia; Alcaín-Martínez, Guillermo; Garcia-Muñoz, Beatriz; Ruiz-Santana, Natalia; Vázquez-Pedreño, Luis; et al. (International Journal of Obesity, 2020)
Objective The intestinal immune response could play an important role in obesity-related comorbidities. We aim to study the profile of duodenal cytokines and chemokines in patients with morbid obesity (MO), its relation with insulin resistance (IR) and the intake of metformin, and with the evolution of MO after sleeve gastrectomy (SG). Research design and methods Duodenal levels of 24 cytokines and 9 chemokines were analyzed in 14 nonobese and in 54 MO who underwent SG: with lower IR (MO-lower-IR), with higher IR (MO-higher-IR), and with type 2 diabetes treated with metformin (MO-metf-T2DM). Results MO-lower-IR had higher levels of cytokines related to Th1, Th2, Th9, Th17, Th22, M1 macrophages, and chemokines involved in the recruitment of macrophages and T-lymphocytes ( p < 0.05), and total (CD68 expression) and M1 macrophages (ITGAX expression) ( p < 0.05) when compared with nonobese patients, but with a decrease in M2 macrophages (MRC1 expression) ( p < 0.05). In MO-higher-IR, these chemokines and cytokines decreased and were similar to those found in nonobese patients. In MO-metf-T2DM, only IL-4 (Th2) and IL-22 (Th22) increased their levels with regard to MO-higher-IR ( p < 0.05). In MO-higher-IR and MO-metf-T2DM, there was a decrease of CD68 expression ( p < 0.05) while ITGAX and MRC1 were similar with regard to MO-lower-IR. We found an association between CXCL8, TNFβ and IL-2 with the evolution of body mass index (BMI) after SG ( p < 0.05). Conclusions There is an association between a higher IR and a lower duodenal immune response in MO, with a slight increase in those patients with metformin treatment. Intestinal immune response could be involved in the evolution of BMI after SG.